Blockchain-Based Secure Data Sharing in Cloud Computing - Zahran Rayyan; Rayyan Mahdi; Syarifal Luthfan (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Cloud computing has revolutionized data storage and management; however, security and privacy concerns remain critical challenges. This paper explores the integration of blockchain technology to enhance data security in cloud environments. A decentralized approach ensures data integrity, authentication, and tamper resistance. The proposed framework leverages smart contracts to enforce access control policies efficiently. Simulation results indicate that our model significantly improves data security without compromising system performance.